Influence of two APS coatings on the high-speed tribological behavior of a contact between titanium alloys. (August 2019) - Marquer, Mathieu; Philippon, Sylvain; Faure, Laurent; Chassaing, Guillaume; Tardelli, Joffrey; Demmou, Karim
Abstract: Contacts between titanium alloys may use an anti-fretting coating on one component. However violent events may cause severe sliding. In the high speed and pressure (up to 60 m/s and 280 MPa) sliding of a non-coated on a coated part, we investigate the influence of the coating (CoCrAlYSiBN or CuNiIn) on the friction coefficient, wear, and microstructural affectations. Both coatings did not significantly influence the friction coefficient but reduced the wear. A scenario based on interface-localized heat explaining the generation of a third body and its influence on the tribological behavior was proposed. The dependence of the mechanical and thermal affectations on the coating material was explained based on the kinetic of the α→β phase transformation of the Ti6Al4V alloy. Graphical abstract: Image 1 Highlights: The coating integrity was preserved with both CoCrAlYSiBN and CuNiIn materials. The two coating materials led to similar friction coefficients and wear volumes. The non-coated part suffered shearing and thermal affectation. Heat localization and third body formation explain the contact behavior. Quicker third body formation led to lower thermal affectation of the slider.